Acute myeloid leukemia during pregnancy: a systematic review and meta-analysis. Issue 3 (4th March 2018) - Horowitz, Netanel A.; Henig, Israel; Henig, Oryan; Benyamini, Noam; Vidal, Liat; Avivi, Irit
Abstract: Data regarding clinical characteristics, therapy, maternal and fetal outcomes of pregnancy-associated acute myeloid leukemia (PA-AML) are limited. This study (including 138 cases published between 1955 and 2013) provides comprehensive assessment of these clinical parameters and may serve as a platform for developing management recommendations. Most patients (58%) received anthracycline–cytarabine-based regimens (ACBRs), which were associated with significantly increased complete remission (CR: 91%). Yet, the maternal overall survival (OS: ∼30%) was relatively low, probably reflecting reduced application of risk-adapted consolidation and allogeneic stem cell transplantation (allo-SCT). Fetal exposure to ACBRs resulted in a live birth rate of 87%, with complications (16%) diagnosed only in chemotherapy-subjected neonates. This study demonstrates safety and efficacy of ACBRs during pregnancy. Therapy and delivery schedule should allow early referral of high-risk patients to allo-SCT. Generation of a pool of high-quality data on PA-AML could contribute to providing evidence-based therapy and lead to improved maternal and fetal survival.